Afrocubanisme au Québec : La rumba guaguanco - Cano, Jocelyn (MUSICultures, 1990)
Hughes Jocelyn Cano compares Cuban music in Montréal and Cuba focusing on a specific genre, the rumba guaguanco.

La rumba de type “guaguanco” : de Cuba à Montréal - Cano, Jocelyn (Université de Montréal, 1998)